How Should the Education System Approach Children with Special Needs? - Anjali Digambar Kamble; Hemlata Vivek Gaikwad (Indonesian Journal of Community and Special Needs Education, 2021)
Education is about supporting children to develop in all aspects of their lives, spiritual, moral, cognitive, emotional, imaginative, aesthetic, social, and physical. The purpose of the study is to evaluate the effective teaching practice for children with special learning needs. Data were taken from the internet, journals. Education should be about enabling all children, in line with their abilities, to live full and independent lives so that they can contribute to their communities, cooperate with other people and continue to learn throughout their lives. Understanding the educational needs of the children in India. This research used a quantitative method to find out their special needs about education. The results showed that students are getting their education special needs with both positive and negative effects. This research paper dealt with the effective practices in Inclusive and Special Needs Education. Inclusive Education means that all students in a school, regardless of their strengths or weaknesses in any area, become part of the school community Why? We conclude that there are many aspects to a child’s development that make up the whole child. Each child has individual strengths, personality, and experiences so particular disabilities will impact differently on individual children.